Violence, Religion, and Trauma: A Social Critique on the Phenomenon of Terrorism in Movies - Samual, Putri Suryani; Priyanto, Sapto (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
The violent and religiously manipulative content of several religious movies can cause trauma to those who view them. This study uses cognitive dissonance theory to analyze how religious movie that highlight aspects of fear in the movie can affect social construction, particularly in light of the possibility of extreme attitudes. Qualitative content analysis using narrative and visual techniques to many key scenes is the methodology employed. The findings demonstrated how the portrayal of religious organizations as purveyors of threatening doctrine that emphasizes punishment affects the psychological strain of the story's characters, leading to internal conflict and a range of responses, such as rejection and extreme tendencies. The results show how authoritative religious teachings might influence psychological and symbolic pressure. To promote critical attitudes and avoid the possible detrimental effects of interpreting teachings that emphasize fear, this research helps clarify the significance of media literacy and the selective distribution of religious beliefs.